General and specific microscopic characteristics of the dorsal tail scales and the spines of the crest in the tuatara Sphenodon pucntatus (Reptilia; Rhynchocephalia; Sphenodontidae). (October 2020) - Alibardi, L.; Meyer-Rochow, V.B.
Highlights: Crest and tail spine scales in the tuatara differ ultrastructurally from each other. Crest and tail spines represent modified scales composed of prevalently of beta proteins as ide from keratins. Corneous beta proteins are abundant in tail ridge but not crest scales. The dermal mesos-layer is particularly well developed in the crest scales. Abstract: Dorsal crest scales and those of the tail spines of the tuatara ( Sphenodon punctatus ) represent different specializations involved in display and protection. Erection of the dorsal crest occurs in males during combat and courtship, but tail spines are not noticeably involved in these activities. In both scale derivatives corneous beta proteins (CBPs, formerly called beta-keratins) and intermediate filaments keratins (IFKs) were determined by immunolabelling. The dermis is dense with few sparse fibrocytes surrounded by collagen bundles, the latter rather randomly oriented in the crest scales. In the tail ridge scales banded collagen I fibrils form more regular, orthogonally aligned bundles of alternating layers with connections to the basal epidermal membrane. A conglomerate of dermal melanonophores and iridophores is present under the epidermis. The iridophores are the likely origin of the whitish colour of the crest. The epidermis shows a thicker beta-layer with serrated/indented corneocytes in the tail scales while the beta layer is reduced in the crest but contains CBPs. A relatively thick mesos layer is present in both scale derivatives, especially in the crest where its role, aside from limiting transpiration, is not known. The alpha-layer is formed by corneocytes with irregular perimeter and sparse desmosomal remnants. The high labelling intensity for CBPs in the beta-layer disappears in the mesos layer but occurs, albeit strongly reduced, in the alpha-layer as in the other body scales. The take-home message is that the dense dermis and its apical beta-layer strengthen mechanically the ridge spines while the crest is mainly supported by the firm but pliable and less dense or regular dermis.